Human herpesvirus 8 (HHV-8) detected in two patients with Kaposi's sarcoma-like pyogenic granuloma. Issue 8 (1st August 2002) - Ryan, P; Aarons, S; Murray, D; Markham, T; O'Sullivan, S; Lyons, F; Lee, G; Fitzgibbon, J
Abstract : Aims: To report the finding of human herpesvirus 8 (HHV-8) in two patients with Kaposi's sarcoma (KS)-like pyogenic granuloma. This form of pyogenic granuloma closely resembles KS histologically and it has been reported that immunohistochemistry in such lesions may be positive for smooth muscle actin and factor VIII related antigen, which are typically negative in KS. In both patients the lesions were positive for CD31, CD34, smooth muscle actin, and factor VIII related antigen, a profile typical of KS-like pyogenic granuloma. The lesions were tested for the presence of HHV-8 DNA, which to date has been consistently found in all types of KS. Methods: The lesions were tested for the presence of HHV-8 DNA using the polymerase chain reaction (PCR). A known HHV-8 positive KS specimen was used as the positive control. Six samples of non-KS vascular skin lesions were used as negative controls for the PCR reaction. Results: Both lesions were positive on PCR for HHV-8 and the specificity of product was confirmed by direct sequencing. None of the six control vascular skin lesions was positive for HHV-8. These results strongly indicate KS as the true diagnosis and are supported by the reported clinical course in both cases. Conclusions: Techniques targeting HHV-8 DNA for detection to confirm a diagnosis of KS are both sensitive and specific. In cases where the differential diagnosis includes KS-like pyogenic granuloma, caution should be taken not to diagnose solely on the basis of immunohistochemistry phenotype. In such cases, PCR targeting HHV-8 DNA sequences is a better diagnostic tool.